LITERASI KEUANGAN SERTA PENGGUNAAN PRODUK DAN JASA LEMBAGA KEUANGAN DI KALANGAN PELJAR - Yughi, Sheila Ardilla; Awaludin, Taufik; Lestari, Ambar Widya; Savitri, Enny; Cahyadi, Eko (LPPM Universitas Pamulang, 2020)
Based on the National Survey of Indonesian Financial Literacy conducted in 2013, it is known that the level of financial literacy of Indonesian people which is classified as well literate is only 21.8% sufficient literate is 75.69% less literate is 2.06% and non-literate is 0.14 %. The main purpose of the National Financial Literacy Strategy is to realize Indonesian people who have a high level of financial literacy so that people can choose and utilize financial products and services to improve welfare. Based on this phenomenon, given the importance of financial literacy for the community especially for students, it is necessary to hold a community service related to financial literacy among students at Al Mubarak High School. The method used is an interactive seminar or education in the field of finance to students in order to manage finances intelligently, so that the low knowledge of the financial industry can be overcome and not easily fooled into investment products that offer high returns in the short term without considering the risks. The results of this dedication activity are that students become more educated with regard to financial literacy and the use of financial institution products and services, which begin with interactive seminars and continue with directed discussions between presenters and students consisting of 69 AL Mubarak high school students, as well as introduction to products and services from financial institutions. The importance of financial literacy for students is expected to make individuals wiser and smarter in managing their assets so that they can provide benefits in supporting individual finances both in the short and long term.